Flossie Teacake's Fur Coat - Davies, Hunter; Illustrated by Hutchins, Laurence (London The Bodley Head, 1982)
A nine-year-old English girl fulfills some of her life-long ambitions when she dons a magical coat and becomes eighteen years old.
Include Illustrations
Keywords: Children's stories -- England -- Magic